Vertebral destruction due to abdominal aortic aneurysm. (2015) - Jiménez Viseu Pinheiro, J.F.; Blanco Blanco, J.F.; Pescador Hernández, D.; García García, F.J.
Highlights: Low back pain is a common cause of medical consultation, and usually supposes a non-malignant prognostic. We report an abdominal aortic aneurism (AAA) as atypical etiology of low back pain. We should consider AAA as other cause of low back pain and routinely examine the abdomen and seek complementary imaging proves when risk factors for AAA are present. Orthopedic surgery for back spine stabilization has to be elective in those cases when vertebral destruction is above 30% and clinic is directly related to spine instability. Abstract: Introduction: Low back pain is a common cause of medical consultation, and usually supposes a non-malignant prognostic. Presentation of case: We report an atypical appearance of low back pain associated to shock and pulsatile abdominal mass that made us diagnose an abdominal aortic aneurysm as reason of vertebral lysis and pain. Discusion: Surgical repair of contained AAA should be directed to secondary re-rupture prevention, with an approximate survival near to 100% at selected patients for elective surgery. Consequently, orthopedic surgery for back spine stabilization has to be elective in those cases when vertebral destruction is above 30% and clinic is directly related to spine instability. Conclusion: We should consider AAA as other cause of low back pain and routinely examine the abdomen and seek complementary imaging proves when risk factors for AAA are present.